Perceptions of parental support buffer against depression for Brazilian youth with interpersonal difficulties. (January 2013) - DeLay, Dawn; Hafen, Christopher A.; Cunha, Josafá M.; Weber, Lidia N. D.; Laursen, Brett
This study examines whether perceptions of parent support buffer against concurrent adolescent depression for youth with interpersonal difficulties. Participants included 398 youth (225 females, 173 males) from public (63.3%) and private (36.7%) schools in Brazil. Adolescents ranged in age from 11 to 14 years ( M = 12.81). Perceptions of parent support moderated concurrent associations between youth reports of peer victimization and depressive symptoms such that youth with high levels of support reported less depression when victimized than youth with low levels of support. Perceptions of parent support also moderated concurrent nonlinear associations between youth reports of family conflict and depressive symptoms. Moderate levels of family conflict were associated with heightened depressive symptoms in youth who reported low levels of support from parents, whereas youth who perceived high levels of support from parents reported heightened depressive symptoms only in conjunction with elevated family conflict.